The rise in female participation in Colombia : fertility, marital status or education? (2013)
Colombia has experienced a secular increase in the labor participation of urban women, going from nearly 47% in 1984 to 65% in 2006. We decompose the evolution of participation into changes in the composition of the population and changes in the participation rates by groups (defined according to the variables that appear most relevant: educational attainment, fertility and marital status). The increase in participation is driven by the increase in the participation rate of married or cohabiting women and women with low educational attainment. Fertility status appears to be less important. Changes in the population composition by educational attainment are also relevant in explaining the increase in participation. However, changes in composition by marital status or fertility are second order effects.